A Comparative Study of Students’ Religious Moderation in Islamic Education Learning - Pandriyani, Yosie Kristin; Atfaliyah, Hodiqotul; Muhtarom, Ali; Qurtuby, Ahmad (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze differences in students’ levels of religious moderation in Islamic Religious Education classes at the junior high school level in Indonesia. The study employs a comparative quantitative approach using a survey method. The sample consisted of 120 students selected through proportional random sampling. The research instrument consisted of a religious moderation questionnaire with 25 items covering four indicators: national commitment, tolerance, anti-violence, and accommodation of local culture. Analysis results showed that the average religious moderation score for students at State Junior High School 1 in Cilegon City was 82.45, while students at State Junior High School 3 in Cilegon City scored an average of 78.10. A comparison test using the Independent Samples t-test yielded a t-value of 3.214 with p = 0.002 (p < 0.05), indicating a significant difference between the two groups. These findings suggest that the level of religious moderation among students at State Junior High School 1 in Cilegon City is higher than that at State Junior High School 3 in Cilegon City. The implications and benefits of this study suggest that schools need to strengthen learning strategies based on dialogue and local culture. These results also serve as a basis for teachers and policymakers to improve religious moderation programs in a structured and sustainable manner.